MORATORIUM ON OIL PALM: ECOLOGICAL RECOVERY OR ECONOMIC SLOWDOWN? - Maesaroh, Syti Sarah; Suroso, Arif Imam; Pahan, Iyung (Universitas Brawijaya, Indonesia, 2018)
The aims of this study are to determine the factors that affect the moratorium policy and its effect on the national production of palm oil. This study used an in-depth interviewwithpairwise comparison questionnaire to experts. Data were analyzed using Analytical Network Process (ANP),consisting of three stages (model construction, model quantification, and analysis). The results showed that law enforcement, sustainability, conflict resolution, deforestation and land conversion were factors that influence the success of the moratorium. The various problems in these factors indicate that the moratorium cannot be done optimally. During sixyears of its implementation, the moratorium impactson the sustainability of palm oil production in Indonesia.Evaluation of moratorium is needed by using quantitative data. Forest deforestation due to oil palm plantation can be used to support the policy analysis.